2009
DOI: 10.1007/s10646-009-0437-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of atrazine on spotted salamander embryos and their symbiotic alga

Abstract: Worldwide amphibian declines have been a concern for biologists for the past several decades. The causes of such declines may include habitat loss, invasive species, pathogens, and man-made chemicals. Agricultural herbicides, in particular, are known to interfere with reproduction in amphibians and are likely contributing to population declines. We tested the effects of the herbicide atrazine on developing spotted salamanders (Ambystoma maculatum) and their symbiotic green alga Oophila amblystomatis. We expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
0
21
1
Order By: Relevance
“…This is in contrast to effects reported by Olivier and Moon (2010), which included complete absence of algal growth and reduced hatching success in egg masses treated with concentrations of atrazine as small as 50 mg/L (nominal; as the formulation Aatrex ® ). Key differences between these studies which may account for these dissimilarities include: 1) stage at initial treatment (stage 10e17 vs. stage 23e29); 2) use of formulated product vs. active ingredient; 3) exposure environment (temperature, light level, and water quality) and 4) nominal vs. measured concentrations.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…This is in contrast to effects reported by Olivier and Moon (2010), which included complete absence of algal growth and reduced hatching success in egg masses treated with concentrations of atrazine as small as 50 mg/L (nominal; as the formulation Aatrex ® ). Key differences between these studies which may account for these dissimilarities include: 1) stage at initial treatment (stage 10e17 vs. stage 23e29); 2) use of formulated product vs. active ingredient; 3) exposure environment (temperature, light level, and water quality) and 4) nominal vs. measured concentrations.…”
Section: Discussioncontrasting
confidence: 88%
“…Laboratorycultured algae (mostly motile cells) were apparently more sensitive to atrazine than algae in whole egg masses (mostly non-motile cells, based on stage) in this study, suggesting that differences in algal life-stage during initial exposure to atrazine could affect sensitivity. However, less than a 10% reduction in optical density was associated with exposure of cultured algae to 50 mg/L atrazine (Table 3), compared to complete elimination of growth at this concentration in Olivier and Moon (2010), so this does not fully explain the difference in results. Perhaps more interestingly, the total population of cells within the egg capsule has been found not to increase beyond stage 25, while mean cell volume increased 3-fold (Bishop and Miller, 2014).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…More recent Ambystoma maculatum-algal exclusion experiments removed algae with 50-400 ug/L of the herbicide atrazine (2-chloro-4-(ethylamino)-6-(isopropylamino)-s-triazine), and recorded similar negative effects on embryonic growth and development (Olivier and Moon 2010). However, atrazine is also known to be a potent amphibian endocrine disruptor, which can cause feminization of male frogs (Hayes et al 2010), and has been shown to cause higher mortality and delayed hatching in Ambystoma barbouri embryos (Rohr et al 2004).…”
Section: Intracapsular Algaementioning
confidence: 88%
“…Numerous detrimental effects have been observed in amphibians including decreases in fat body size and liver weights in Xenopus laevis tadpoles, decreased spermatogenesis and fertility in male X. laevis, and reduced successful egg hatching in spotted salamander embryos, Ambystoma maculatum (Zaya et al 2011;Hayes et al 2010;Olivier and Moon 2010). In humans, atrazine Disposition of atrazine metabolites in switchgrass has been linked to various cancers including breast, brain, ovarian, stomach, and testicular cancer (Patlak 1996;Powell et al 2011).…”
Section: Introductionmentioning
confidence: 99%